Peripilar Sign in Androgenetic Alopecia: Does It Really Indicate Peripilar Infiltrate? - Abdalla , Dina; Bosseila, Manal; R.E. Abdel-Halim, Mona; Sany, Iman (Dermatology Practical & Conceptual, 2024)
Introduction: Peripilar sign (PPS) is a trichoscopic sign that was first described in androgenetic alopecia (AGA) and is thought to reflect the presence of perifollicular infiltrate (PFI) in histopathology.Objectives: To study PPS in a cohort of patients with AGA and to assess its validity as a sign indicative of PFI.Methods: One hundred patients with AGA (confirmed by trichoscopic examination) were recruited in this cross-sectional study. From those patients, frontal scalp biopsy was done for two subgroups, 22 patients with PPS and 23 patients without PPS. Both groups were compared as regards the presence of PFI.Results: Peripilar sign was present in 50% of the 100 studied cases. No significant difference existed between those with and those without PPS as regards PFI. Peripilar sign was significantly more encountered in patients with skin type III (p=0.001). Its absence was significantly associated with lower interpretability of yellow dots (p<0.001) and their scores were significantly positively correlated (r=0.498, p<0.001). Peripilar sign was significantly associated with absent melanophages histopathologically (p=0.011).Conclusion: Peripilar sign as a trichoscopic sign in AGA does not reflect PFI. It represents a dark color more encountered in patients with lighter skin types. This can be explained by the increased contrast between the dark PPS and the lighter surrounding skin in lighter skin types. Further studies using melanocyte markers and Masson Fontana's stain are needed to further verify the cause of this peri-follicular dark color.